The Ways of Improving the Efficiency of the Import Substitution Strategy of Russian Federation - Shabalina, L.V.; Karaman, E.G. (Економічний вісник Донбасу, 2015)
The dynamics and structure of Russian Federation import in the current geopolitical situation were analyzed. The international experience and the types of import substitution policy were studied. Improvements and development of the innovative activity were proposed. The creation of national support center was grounded.